Determination of product distribution strategy with direct shipping and cross-docking methods - Alvyn Tjo; Anita C. Sembiring; Chandra Wijaya; Yulio Simarmata (Institute of Computer Science (IOCS), 2023)
The right product distribution strategy is a decision that must be considered by the company to increase optimal profits, because an effective and efficient strategy can reduce distribution costs. A tire manufacturing company experiences difficulties in choosing the right product distribution strategy, because shipping costs are always increasing. For this reason, research was conducted in order to be able to provide optimal strategy proposals to be implemented in the company. From the results of the research and data processing carried out, there are two tests for the direct delivery strategy and the warehouse delivery strategy. The research described in the given statement contributes to the field of product distribution strategy, specifically in the context of a tire manufacturing company facing increasing shipping costs. Testing of these strategies is carried out using the Vehicle Routing Problem (VRP) method to calculate the total optimal distribution cost of each strategy. The mathematical model in this study was solved using optimization software. Based on the research results, the delivery strategy through the warehouse is better than the direct delivery strategy and the cross-docking strategy with a total cost of Rp. 3,213,200. This result is smaller than the cross-docking of IDR 3,544,000 each. This shows that the warehouse delivery strategy can save costs by 8.86%. The research concludes that the warehouse delivery strategy offers the most favorable results in terms of cost savings and efficiency compared to the direct delivery and cross-docking strategies.